Evaluasi Terhadap Implementasi Manajemen Perpustakaan Sebagai Sarana Pembelajaran di SMA Muhammadiyah 1 Gresik - Muhammad Afifi Rahman (Indo-MathEdu Intellectuals Journal, 2023)
In Permendikbud No. 3 of 2020 concerning Standards for Learning facilities and infrastructure are the minimum criteria regarding facilities and infrastructure in accordance with the needs of the content and learning process in the framework of fulfilling graduate learning outcomes. In general, this study aims to evaluate the implementation of learning-based library management organized by SMA Muhammadiyah 1 Gresik. Based on its purpose, this research was designed as a qualitative research. In this case the population in this study are students, teachers, foundation owners, and school principals. The research subjects were a portion of the population at SMA Muhammadiyah 1 Gresik. The results obtained in this study are expected to provide an explanation of how learning-based library management is implemented in terms of learning process standards. The results showed that the maintenance of learning-based library facilities at SMA Muhammadiyah 1 Gresik was carried out in the context of efficiency and effectiveness. Continuous (regular, routine) maintenance is carried out in this school library. Library maintenance involves teachers, librarians, and student